Mobile Cinerama: A work of the architect Emilio Pérez Piñero - García González, Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Cinerama film show is a benchmark in big screen technology. Thanks to Fred Waller and Hazard Reeves, Cinerama rose in popularity. This led to the creation of traveling mobile pavilions. Cinesa initiated the development of the mobile Cinerama in Spain, due to the lack of movie theaters. In 1966, they turned to Emilio Pérez Piñero to design a mobile pavilion that imitated Welton Becket’s Cinerama Dome, which followed Richard Buckminster Fuller’s geodesic dome patent. However, Piñero designed a patent of his own known as the spherical directive reticular dome.